Effectiveness of Lactobacilli cell-free supernatant and propolis extract microcapsules on oxidation and microbiological growth in sardine burger. (December 2021) - Kuley, Esmeray; Yazgan, Hatice; Özogul, Yesim; Ucar, Yilmaz; Durmus, Mustafa; Özyurt, Gülsün; Ayas, Deniz
Abstract: Antibacterial and antioxidative effects of microencapsulated Lactobacillus reuteri ATCC 55730 cell-free supernatant (CFS) alone (MCFS) or in combination with propolis water (MPW) and ethanolic extract (MPE) on sardine burger were investigated at 4 ± 1 °C for 15 days. Morphological properties of microcapsules were determined by scanning electron microscopy (SEM). Microcapsules had rough cylindrical structure and wrinkled morphology (especially the microcapsules with aqueous propolis extract). The use of microcapsules with propolis extracts maintained the sensory quality of sardine burgers. MCFS, MPW and MPE groups had 3 days longer sensorial shelf life although burgers with propolis extract (MPW and MPE groups) were more preferred by panellists. MCFS, MPW and MPE groups had a lower content of TVB-N than control. CFS from L. reuteri and propolis combinations in microencapsulation showed stronger antioxidative effect for fish burger. The highest TBA and FFA values were observed for the control (10.78 MDA/kg vs 12.98% oleic acid) and MCFS (10.67 MDA/kg vs 12.51% oleic acid) at the end of storage. Microbiological upper limit of 7 log cfu/g did not exceed for all groups during storage. Microencapsulated CFS from L. reuteri and mainly propolis water extract combinations induced a lower bacterial growth in fish burger. The results revealed that the use of Lactobacilli supernatant alone has a weak antioxidative effect whereas the microcapsules with propolis extract have the potential to be used as antioxidant, by enhancing quality characteristics of burger. Highlights: L. reuteri ATCC 55730 cell free supernatant (CFS) was microencapsulated. Lactobacilli CFS with/without propolis extract provide longer shelf-life for burger. Use of Lactobacilli CFS alone has a weak antimicrobial and antioxidative effect. Combined use of CFS and propolis extract enhance quality characteristics of burger.